PFAS Experts Symposium 2: PFAS Toxicology and Risk Assessment in 2021—Contemporary issues in human and ecological risk assessment of PFAS. Issue 1 (17th January 2022) - Zodrow, Jean; Vedagiri, Usha; Sorell, Tamara; McIntosh, Lisa; Larson, Emily; Hall, Linda; Dourson, Michael; Dell, Linda; Cox, Douglas; Barfoot, Krista; Anderson, Janet
Abstract: This paper summarizes key information on topics of contemporary interest in human and ecological per‐ and polyfluoroalkyl substance (PFAS) risk assessment, which were discussed at the PFAS Experts Symposium 2. For human health, the discussion focused on the toxicologic and epidemiologic endpoints and exposure assumptions that contribute to differences in PFAS regulatory criteria. For ecological risk, the discussion assessed the current state of the science available to support ecological screening levels and identified key data gaps and uncertainties in our understanding of ecological exposure and toxicity. Finally, the paper summarizes a panel discussion that addressed the challenges and uncertainties of regulating PFAS as a class.